Diabetes Insipidus Complicating Management in a Child with COVID-19 and Multiorgan System Failure: A Novel Use for Furosemide - Sara D. Gungor; Robert P. Woroniecki; Erin Hulfish; Katherine V. Biagas (Case Reports in Critical Care)
Judicious balance of fluids is needed for optimal management of acute respiratory distress syndrome (ARDS). Achieving optimal fluid balance is difficult in patients with disorders of fluid homeostasis such as diabetes insipidus (DI). There is little data on the use of Furosemide to aid in balancing fluid and electrolytes in patients with DI. Here, we present a critically ill 11-year-old female with developmental delay, septo-optic dysplasia, central DI, and respiratory failure secondary to COVID-19 ARDS. She required careful titration of a Vasopressin infusion in addition to IV Furosemide for successful management of fluid and electrolyte derangements. On admission, she demonstrated high-volume urine output with mild hypernatremia (serum sodium 156 mmol/L). Despite her maximum Vasopressin infusion rate of 8 mU/kg/hr, by day two of admission, she voided a total of 4 L resulting in severe hypernatremia (serum sodium 171 mmol/L). With continually high Vasopressin infusion rates, her overall fluid balance became increasingly net positive, although her hypernatremia persisted. Her ARDS continued to worsen. After 48 hours of the addition of intermittent Furosemide, successful diuresis along with resolution of hypernatremia was achieved. The combination of IV Furosemide with Vasopressin infusion resulted in tailored diuresis and more controlled titration of serum sodium levels than adjustment in Vasopressin and fluids alone. These results are in contradistinction to the published literature, which focuses on the use of thiazide diuretics in managing DI. This experience highlights the potential for loop diuretics to aid in establishing a desired fluid and electrolyte status in managing patients with both DI and ARDS.